2019
DOI: 10.1002/hep.30631
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4‐Alpha Is Essential for the Active Epigenetic State at Enhancers in Mouse Liver

Abstract: Cell-fate determination is influenced by interactions between master transcription factors (TFs) and cis-regulatory elements. Hepatocyte nuclear factor 4 alpha (HNF4A), a liver-enriched TF, acts as a master controller in specification of hepatic progenitor cells by regulating a network of TFs to control onset of hepatocyte cell fate. Using analysis of genome-wide histone modifications, DNA methylation, and hydroxymethylation in mouse hepatocytes, we show that HNF4A occupies active enhancers in hepatocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 46 publications
5
43
1
Order By: Relevance
“…Specifically, for HepG2, HNF4A, NR2F6, JDP2, and FOX, family motifs showed a twofold preference for distal, enhancer HOT loci, and ETS and SP family motifs had a threefold bias for proximal, promoter HOT loci. These findings agree with previous studies that have found HNF4A occupancy at enhancers to be essential for activity in mouse hepatocytes (Thakur et al 2019) and a strong promoter bias for the ETS family of motifs (Hollenhorst et al 2007). The level of sequence conservation of driver TF motifs was higher in HOT loci (Supplemental Fig.…”
Section: Hot Loci Are Enriched For Promoter and Enhancer Regions Nearsupporting
confidence: 92%
“…Specifically, for HepG2, HNF4A, NR2F6, JDP2, and FOX, family motifs showed a twofold preference for distal, enhancer HOT loci, and ETS and SP family motifs had a threefold bias for proximal, promoter HOT loci. These findings agree with previous studies that have found HNF4A occupancy at enhancers to be essential for activity in mouse hepatocytes (Thakur et al 2019) and a strong promoter bias for the ETS family of motifs (Hollenhorst et al 2007). The level of sequence conservation of driver TF motifs was higher in HOT loci (Supplemental Fig.…”
Section: Hot Loci Are Enriched For Promoter and Enhancer Regions Nearsupporting
confidence: 92%
“…HNF4 additionally controls cell identity and function of endodermal organs through tissue-specific modifications of the chromatin structure. In murine hepatocytes, HNF4A is essential for establishing and maintaining active histone and DNA epigenetic states at CRMs through interaction with E1A Binding Protein P300 (EP300) and Tet Methylcytosine Dioxygenase 3 (TET3), respectively [ 108 ]. The role of HNF4A in the maintenance of an active chromatin state at liver identity genes is further illustrated by the proposal that it stabilizes histone H3 lysine 4 dimethylation (H3K4me2) at hepatic CRMs [ 109 ].…”
Section: Mechanisms Of Action In the Control Of Cell Identity By Hmentioning
confidence: 99%
“…In order to shed light on mechanism involved in the regulation of HSD17B6, we first tried to find out transcription factors regulating HSD17B6. It has been recently reported that HNF4A, a liver-enriched transcription factor, could upregulate gene expression in hepatocytes by binding the enhancers of target genes [24]. There was a significant positive correlation between HSD17B6 and HNF4A transcript levels both in normal and HCC tissues from both TCGA and ICGC LIRI-JP datasets ( Fig.…”
Section: Transcriptional Regulation Of Hsd17b6 In Hepatocellular Carcmentioning
confidence: 70%